2011
DOI: 10.1182/asheducation-2011.1.525
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Sideroblastic Anemias: Iron and Heme Lost in Mitochondrial Translation

Abstract: The congenital sideroblastic anemias (CSAs) are an uncommon, diverse class of inherited hematopoietic disorders characterized by pathological deposition of iron in the mitochondria of erythroid precursors. In recent years, the genetic causes of several clinically distinctive forms of CSA have been elucidated, which has revealed common themes in their pathogenesis. In particular, most, if not all, can be attributed to disordered mitochondrial heme synthesis, iron-sulfur cluster biogenesis, or pathways related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 43 publications
1
94
0
3
Order By: Relevance
“…In the remaining forms of porphyria, erythrocyte non-heme protoporphyrins generally lie within the reference range [13]. Lead and other heavy metal intoxication [15][16][17] and a variety of sideroblastic [18] and inherited microcytic anemias [19] may also be responsible for alterations in erythrocyte PPIX and ZnPP. A recent study found decreased PPIX fluorescence in erythrocytes from diabetic compared to non-diabetic mice, suggesting the possible use of PPIX as a diagnostic marker for monitoring of diabetes [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the remaining forms of porphyria, erythrocyte non-heme protoporphyrins generally lie within the reference range [13]. Lead and other heavy metal intoxication [15][16][17] and a variety of sideroblastic [18] and inherited microcytic anemias [19] may also be responsible for alterations in erythrocyte PPIX and ZnPP. A recent study found decreased PPIX fluorescence in erythrocytes from diabetic compared to non-diabetic mice, suggesting the possible use of PPIX as a diagnostic marker for monitoring of diabetes [20].…”
Section: Introductionmentioning
confidence: 99%
“…PUS1 facilitates conversion of uridine to its isomer pseudouridine (ψ), which is thought to stabilize RNA secondary structures. 133 The PUS1 mutations decrease the modification of both mitochondrial and cytoplasmic tRNAs, and the disease is associated with decreases in respiratory complexes I and IV; meanwhile, the mutations in YARS2 result in a global decrease in the abundance and synthesis of mitochondrial respiratory complex proteins encoded by the mitochondrial, but not the nuclear, genome. Although the defects in mitochondrial respiration in patients with diseaseassociated PUS1 and YARS2 mutations are likely to result from impaired mitochondrial protein translation, the mechanism by which these mutations cause accumulation of mitochondrial iron and sideroblastic anemia is not known.…”
Section: Mitochondrial Dysfunction and Autophagy In The Pathogenesis mentioning
confidence: 99%
“…132 Pearson marrow-pancreas syndrome is a disorder characterized by bone marrow and exocrine pancreas insufficiency. 133,134 Patients are heteroplasmic for mitochondrial genomic deletions, with almost half of the patients having a canonical 4,977-bp deletion that involves mtDNA-encoded subunits of respiratory complex I (NADH dehydrogenase), complex IV (cytochrome C oxidase), and complex V (ATP synthase), as well as several mttRNA genes. Patients often present as infants with a variety of signs and symptoms, including failure to thrive, lactic acidosis, malabsorption, myopathy, and liver dysfunction.…”
Section: Mitochondrial Dysfunction and Autophagy In The Pathogenesis mentioning
confidence: 99%
“…3 Mutations in a GATA transcription factor-binding site located in a transcriptional enhancer element in intron 1 of the ALAS2 gene have also been reported. 4,5 Most ALAS2 mutations responsible for sideroblastic anemia are partial loss-of-function alleles affecting heme biosynthesis.…”
Section: Classification Of Sideroblastic Anemiasmentioning
confidence: 99%
“…3 The 2 most common congenital sideroblastic anemias are X-linked sideroblastic anemia (XLSA) attributable to germline mutations in ALAS2 and the autosomal recessive sideroblastic anemia attributable to mutations in SLC25A38.…”
Section: Classification Of Sideroblastic Anemiasmentioning
confidence: 99%